2016
DOI: 10.1021/acs.jafc.6b02077
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR: A Novel Approach To Determining the Thermodynamic Properties of Acetaldehyde Condensation Reactions with Glycerol, (+)-Catechin, and Glutathione in Model Wine

Abstract: As wine oxidizes, ethanol is converted to acetaldehyde, but its accumulation is not predictable, due to poorly characterized reactions with alcohols, SO2, thiols, flavanols, and others. Measurement of these components has been thwarted by equilibria into the other forms during sample preparation. NMR spectra can be taken on intact samples and is thus ideal for this situation. Equilibria of acetaldehyde with glycerol, (+)-catechin, and glutathione were studied separately in model wine solutions at pH 3-4 by (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 48 publications
(96 reference statements)
4
36
1
Order By: Relevance
“…This showed that these four selected heterocyclic acetal alcohols were all well correlated with acetaldehyde. This close correlation also shows that it may be possible to relate the dioxane or dioxolane levels to acetaldehyde levels in wine, as reported recently …”
Section: Resultssupporting
confidence: 83%
“…This showed that these four selected heterocyclic acetal alcohols were all well correlated with acetaldehyde. This close correlation also shows that it may be possible to relate the dioxane or dioxolane levels to acetaldehyde levels in wine, as reported recently …”
Section: Resultssupporting
confidence: 83%
“…. After the first two days of oxidation, the quantity of acetaldehyde dramatically decreases, consistently with the involvement in numerous reactions owing to the great reactivity of this electrophile compound (Peterson & Waterhouse, ). Enological tannins determine an increase in the production of acetaldehyde probably owing to the presence of more structures containing O‐diphenols (Danilewicz, ; Waterhouse & Laurie, ) and/or to traces of metal catalysts present as contaminants of enological tannin preparations.…”
Section: Resultsmentioning
confidence: 99%
“…Acetaldehyde in alcoholic beverages can be produced by yeasts and acetic bacteria or from the oxidation reaction of alcohol and phenolic compounds . However, the electrophilicity of acetaldehyde leads to its participation in reversible reactions with various nucleophiles in alcoholic beverages, including alcohols, thiols, sulfur dioxide and flavonoids . In acidic conditions, acetaldehyde reacts easily with ethanol to generate diethylacetal .…”
Section: Introductionmentioning
confidence: 99%
“…observed the acetaldehyde and acetal from distillation cut, raw liquor and Chinese finished liquor . Aged and micro‐oxygenated wines were monitored in production by sensory analysis or by measuring acetaldehyde . During the brewing process, the determination and quantitative analysis of acetaldehyde could assist in the evaluation of complete and proper fermentation; improper fermentation resulted in reprocessing or dumping of beer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation